Laser absorption spectroscopy of rare and doubly substituted carbon dioxide isotopologues - Prokhorov, Ivan; Kluge, Tobias; Janssen, Christof (Analytical chemistry, 2019)
Unambiguous detection of the clumped carbon dioxide isotopologue 13C16O18O with isotope ratio mass spectrometry is difficult due to isobaric interference on m/z = 47. We present an analytical technique based on direct absorption laser spectroscopy for precise, direct and simultaneous detection of all isotopologues involved in the isotope exchange reaction 12C16O2 + 13C16O18O ↔ 12C16O18O + 13C16O2 and of 12C16O17O. The achieved precision of 2 × 10-5 for the 13C16O18O/13C16O2 and 12C16O18O/12C16O2 isotopologue ratios allows the equilibrium constant K of the isotope exchange reaction to be determined with an external reproducibility of better than 2 × 10-5 (1σ) after 9 reference-sample comparisons. Each comparison requires 7 min. The isotopic composition of the pure gas can be simultaneously analyzed with a precision of 0.05‰ (1σ) for δ13C and δ18O and 0.15‰ (1σ) for δ17O. The instrument deploys two interband cascade lasers (ICL) with center wavelengths of 4.3 and 4.4 μm. A custom-built optical cell has been designed for single pass and multi pass optical paths (path length ratio 1:100); it allows simultaneous detection of rare and abundant isotopologues. The setup is capable to analyze pure CO2 samples of ∼100 μmol.
Gesehen am 15.04.2020